2022
DOI: 10.5455/javar.2022.i607
|View full text |Cite
|
Sign up to set email alerts
|

Sperm kinetics of Egyptian buffalo bulls (Bubalus bubalis) affected by the red laser postfreezing

Abstract: Objective: To improve the fertilizing ability of frozen buffalo semen using the more beneficial, accurate, and cheap technique of laser irradiation at specific wavelengths and exposure times. Materials and Methods: The red laser source (625 nm) was used in this study with 5 watts output power and for the irradiation of the semen samples for 5 min; the laser focus spot area was 1 cm2. Thirty straws belonging to five buffalo bulls were used in this study. Results: The results show that total motility (%) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is reported that buffalo semen is more sensitive to freezing and thawing than bull semen, resulting in lower fertilization potential (Dessouki et al, 2022). The value of sperm motility after thawing in this study follows SNI for frozen buffalo semen No.…”
Section: Discussionmentioning
confidence: 53%
“…It is reported that buffalo semen is more sensitive to freezing and thawing than bull semen, resulting in lower fertilization potential (Dessouki et al, 2022). The value of sperm motility after thawing in this study follows SNI for frozen buffalo semen No.…”
Section: Discussionmentioning
confidence: 53%
“…According to the method of Dessouki et al [ 35 ], the software CASA sperm analyzer (Sperm Vision; Ref: 12520/5000; Minitube Hauptstrae 41. 84184 Tiefenbach, Germany) was applied to provide more information on the live images of various sperm motion characteristics captured by the Olympus computer-assisted microscope.…”
Section: Methodsmentioning
confidence: 99%
“…However, Van de Hoek et al (2022) highlighted that CASA analysis provides essential information for semen quality assessment. Furthermore, using CASA, Dessouki et al (2022) examined buffalo semen and discovered variations in sperm motility and velocity parameters between fresh and frozen-thawed samples.…”
Section: Kinematics Of Fresh and Frozen Ram Spermmentioning
confidence: 99%